Avaliação da atividade antimalárica e antimicrobiana de geissospermum argenteum Woodson e Minguartia guianensis Aubl coletadas em Roraima - Camargo, Marlene Rodrigues Marcelino (2011)
Among the natives species from the Amazon Forest used by traditional populations in the treatment of various health problems, including, malaria, wich in Brazil and in the world remains a serious public health problem, are Geissospermum argenteum Woodson, an Apocynaceae, and Minquartia guianensis Aubl, Olacaceae family. Another important health problem is the microbial infections, because the microorganisms have developed resistence to antimicrobial agents. In this work, samples were collected from bark, leaves and twigs of G.argenteum and M. guianensis in a forestall area in Apiaú village, city of Mucajaí – RR. The samples were extracted by hot methanol and water extraction, resulting in methanol and aqueous extracts. Sample of methanol extract of bark of G.argenteum was submitted to liquid-liquid partitioning, resulting in fractions hexane, chloroform, ethyl acetate and methanol/water. The chloroform fraction was selected for fractionation using chromatography colunn and solvent gradient system, resulting in 38 fractions, which were analyzed by TLC and the fraction Cr10 was selected for preparative chromatography, from which the fraction F6 was obtained, analyzed in CCD was positive for alkaloids. The methanol and aqueous extracts of both species and fractions of extracts from primary G.argenteum were tested in vitro assays for antimalarial activity against the chlroquine-resistant K1 Plasmodium falciparum at concentrations of 50 and 5 mg/mL. Subsequently, active samples were evaluated in 7 diluitions to establish the dose-response and median inhibitory concentration values (IC50). Samples from two species were also tested against bacterial strains, Staphylococcus aureus, Streptococcus mutans and Escherichia coli, and against the yeast Candida albicans. Antimicrobial activity was evaluated by agar diffusion and minimum inhibitory concentration (MIC) by microdilution plates. For fractions of ethyl acetate, chloroform, hexane and water-alcohol obtained from barks of G.argenteum, fraction Cr10 and bioautography was performed fo S. aureus. Antimalarial activity in the methanol extract of bark was active, with IC50 of 4,6 mg/mL and chloroform fraction obtained from bark of G.argenteum was also active with IC50 of 2,0 mg/mL. The extracts of M. guianensis were considered inactive for antimalarial activity. In antimicrobial activity by agar diffusion, extracts of G.argenteum were partially active against S. aureus, S. mutans and inactive against E. coli and C. albicans. The MIC for S. aureus was 0,63 mg/mL per fraction methanol/water, S. mutans, MIC of 0,63 mg/mL and C. albicans with an MIC of 0,63 mg/mL. For the strain of E.coli there was no activity. Extracts of M. guianensis were active against the S. aureus and C. albicans by agar diffusion and presented more than 1 mg/mL MIC for S aureus, S.mutans and C. albicans. The extracts of M. guianensis were inactive against E. coli.